Cross-Reactive Fc-Mediated Antibody Responses to Influenza HA Stem Region in Human Sera Following Seasonal Vaccination - Nishiyama, Ayae; Nogimori, Takuto; Masuta, Yuji; Matsuura, Tomoka; Kase, Tetsuo; Kondo, Kyoko; Ohfuji, Satoko; Nakagama, Yu; Kaku, Natsuko; Nakagama, Sachie; Nitahara, Yuko; Takahashi, Yoshimasa; et al. (Vaccines (Basel), 2025)
Background: Current influenza A vaccines primarily induce neutralizing antibodies targeting the variable hemagglutinin (HA) head domain, limiting their effectiveness against diverse or emerging influenza A virus (IAV) subtypes. The conserved HA stem domain, particularly the long α-helix (LAH) epitope, is a focus of universal vaccine research due to its cross-protective potential. Additionally, Fc-mediated functions such as antibody-dependent cellular cytotoxicity (ADCC) and antibody-dependent cellular phagocytosis (ADCP) are recognized as important protective immune mechanisms. This study evaluated IgG responses to the HA head, stem, and LAH regions and assessed cross-reactive potential through neutralization, ADCC, and ADCP assays. Methods: IgG responses to the HA head, stem, and LAH regions were measured in vaccinated individuals. Functional assays were conducted for neutralization, ADCC, and ADCP to evaluate the association between antibody levels and immune function. Results: The results showed that HA head-specific IgG increased significantly after vaccination in 50 individuals, whereas stem-specific IgG increased by 72% and LAH-specific IgG by 12–14%. Among the induced antibody subclasses, IgG1 was predominantly increased. Neutralization titers were detected in viruses of the same strain as the vaccine strain, but not in classical or pandemic strains (H5N1, H7N9). HA stem-specific IgG1 antibody titers showed a significant correlation with ADCC/ADCP activity breadth, but no correlation was observed with neutralization breadth. Conclusion: These findings suggest that although current influenza vaccines can induce HA stem-targeted cross-reactive antibodies, their quantity may be insufficient for broad cross-protection, underscoring the need for improved vaccine strategies.